Song of the hummingbird - Limón, Graciela (Arte Público Press, 1996)
An Aztec princess describes the Spanish conquest of Mexico. She is Huitzitzlin, 82, of the court of Montezuma and she tells her tale to a priest so history will know who the Aztecs really were. By the author of The Memories of Ana Calderon.